Attribution of Large‐Scale Climate Patterns to Seasonal Peak‐Flow and Prospects for Prediction Globally. Issue 2 (9th February 2018) - Lee, Donghoon; Ward, Philip; Block, Paul
Abstract: Flood‐related fatalities and impacts on society surpass those from all other natural disasters globally. While the inclusion of large‐scale climate drivers in streamflow (or high‐flow) prediction has been widely studied, an explicit link to global‐scale long‐lead prediction is lacking, which can lead to an improved understanding of potential flood propensity. Here we attribute seasonal peak‐flow to large‐scale climate patterns, including the El Niño Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), North Atlantic Oscillation (NAO), and Atlantic Multidecadal Oscillation (AMO), using streamflow station observations and simulations from PCR‐GLOBWB, a global‐scale hydrologic model. Statistically significantly correlated climate patterns and streamflow autocorrelation are subsequently applied as predictors to build a global‐scale season‐ahead prediction model, with prediction performance evaluated by the mean squared error skill score (MSESS) and the categorical Gerrity skill score (GSS). Globally, fair‐to‐good prediction skill (20% ≤ MSESS and 0.2 ≤ GSS) is evident for a number of locations (28% of stations and 29% of land area), most notably in data‐poor regions (e.g., West and Central Africa). The persistence of such relevant climate patterns can improve understanding of the propensity for floods at the seasonal scale. The prediction approach developed here lays the groundwork for further improving local‐scale seasonal peak‐flow prediction by identifying relevant global‐scale climate patterns. This is especially attractive for regions with limited observations and or little capacity to develop flood early warning systems. Key Points: Attribution of long‐lead large‐scale climate signals to seasonal peak‐flow is identified globally Season‐ahead seasonal peak‐flow prediction models are constructed globally Fair‐to‐good prediction skill is evident for many locations, most notably data‐poor regions (e.g., West and Central Africa)